2021
DOI: 10.3390/plants10020378
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Light Does Not Compromise Growth and Yield in Mini-Cucumber Greenhouse Production with Supplemental LED Light

Abstract: Continuous lighting (CL, 24h) can reduce the light intensity/light capital costs used to achieve the desired amount of light for year-round greenhouse vegetable production in comparison to short photoperiods of lighting. However, growth under CL has led to leaf injury characterized by chlorosis unless a thermoperiod or alternating light spectrum during CL is used. To date, there is no literature relating to how cucumbers (Cucumis sativus) respond to CL with LEDs in a full production cycle. Here, we evaluated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 47 publications
0
17
1
Order By: Relevance
“…In contrast to our current study, the use of monochromatic blue light at 100 μmol m –2 s –1 ( Velez-Ramirez et al, 2017 ) or 150 μmol m –2 s –1 ( Matsuda et al, 2016 ) during the night produced a high degree of injury in tomatoes. However, our previous studies on tomato ( Lanoue et al, 2019 ) and cucumber ( Lanoue et al, 2021b ) differ from this trend and indicate that the use of low intensity monochromatic blue light (50 μmol m –2 s –1 ) during the night was able to avert injury. In this study, nighttime blue light was considerably higher than the light compensation point ( Table 2 ), and between that used in Velez-Ramirez et al (2017) and Lanoue et al (2019) , and drove appreciable amounts of photosynthesis in 16W + 8B and 16W + 8BFR during the night ( Figure 3B ) without causing injury ( Figures 4 , 5 ).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…In contrast to our current study, the use of monochromatic blue light at 100 μmol m –2 s –1 ( Velez-Ramirez et al, 2017 ) or 150 μmol m –2 s –1 ( Matsuda et al, 2016 ) during the night produced a high degree of injury in tomatoes. However, our previous studies on tomato ( Lanoue et al, 2019 ) and cucumber ( Lanoue et al, 2021b ) differ from this trend and indicate that the use of low intensity monochromatic blue light (50 μmol m –2 s –1 ) during the night was able to avert injury. In this study, nighttime blue light was considerably higher than the light compensation point ( Table 2 ), and between that used in Velez-Ramirez et al (2017) and Lanoue et al (2019) , and drove appreciable amounts of photosynthesis in 16W + 8B and 16W + 8BFR during the night ( Figure 3B ) without causing injury ( Figures 4 , 5 ).…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, the feasibility of CL strategies hinges on whether the production (yield and quality) is equal to or greater than the conventional 16 h photoperiod lighting (control, 16W in this study). Due to their unique attributes, LEDs allow for the use of a dynamic CL strategy which employs a reduction in light intensity and/or change in spectral composition between day and night periods, which has been shown to eliminate or reduce injury in lettuce ( Ohtake et al, 2018 ), tomato ( Matsuda et al, 2016 ; Lanoue et al, 2019 ; Pham and Chun, 2020 ), and cucumber ( Lanoue et al, 2021b ). In this study with peppers, we showed that plants grown under two dynamic CL strategies (16W + 8B and 16W + 8BFR) were able to avert injury and maintain fruit yield and size (grade) when compared to the 16h control (16W; Figures 3 , 5 , 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, if photoperiod-related injury can be avoided, an increase in plant growth and yield is theoretically possible [ 8 ]. The use of wavelength-specific LEDs has shown promise in reducing photoperiod-related injury during the vegetative growth stage [ 14 ]; however, little is known about how the use of wavelength-specific LEDs will affect the yield of high-wire-fruiting vegetables during extended photoperiods [ 7 , 40 ]. Between the months of February and April, those which followed the photoperiod-related injury in leaves, the average fruit weight (size, g fruit −1 ) was observed to decrease in both 23 h lighting treatments ( Figure 5 and Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%